sin n x + cos n x \sin^{n}x+\cos^{n}x

Algebra Level 4

Determine the largest positive integer n n such that sin n x + cos n x 1 n \sin^{n}x+\cos^{n}x\ge \frac{1}{n} holds true for all real numbers x x .


The answer is 8.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Leonel Castillo
Jun 5, 2018

It is clear that for n 2 n \leq 2 the inequality is trivial so suppose that n 2 n \geq 2 . Then, by the power mean inequality:

sin n x + cos n x 2 n sin 2 x + cos 2 x 2 = 1 2 \sqrt[n]{\frac{\sin^n x + \cos^n x}{2}} \geq \sqrt{ \frac{\sin^2 x + \cos^2 x}{2}} = \sqrt{\frac{1}{2}} Re-arranging the important parts of this we get: sin n x + cos n x 2 ( 1 2 ) n 2 \sin^n x + \cos^n x \geq 2 \left(\frac{1}{2}\right)^{\frac{n}{2}}

So if n n is an integer such that the inequality in the problem does not hold, it must be that 2 ( 1 2 ) n 2 < 1 n 2 \left(\frac{1}{2}\right)^{\frac{n}{2}} < \frac{1}{n} . This inequality holds for n 9 n \geq 9 (check proof below). However, this condition is necessary but not sufficient so let's confirm that n 9 n \geq 9 does not work: Consider x = π 4 x = \frac{\pi}{4} which implies sin x = cos x = 2 2 \sin x = \cos x = \frac{\sqrt{2}}{2} . Then sin n x + cos n x = 2 ( 2 2 ) n = 2 ( 1 2 ) n 2 < 1 n \sin ^n x + \cos ^n x = 2\left( \frac{\sqrt{2}}{2} \right)^n = 2 \left(\frac{1}{2}\right)^{\frac{n}{2}} < \frac{1}{n} .

Thus, the given inequality holds up to n = 8 n=8 .

2 ( 1 2 ) n 2 < 1 n 0. 5 n 2 < 0.5 n 2 \left(\frac{1}{2}\right)^{\frac{n}{2}} < \frac{1}{n} \iff 0.5^{\frac{n}{2}} < \frac{0.5}{n} . Let u = n 2 u = \frac{n}{2} , then 0. 5 n 2 < 0.5 n ( 1 2 ) u < 1 4 u u log 2 < log 4 u log 4 u u log 2 < 1 2 u + log 2 u u < 1 0.5^{\frac{n}{2}} < \frac{0.5}{n} \iff \left( \frac{1}{2} \right)^u < \frac{1}{4u} \iff -u \log 2 < - \log 4u \iff \frac{\log 4u}{u \log 2} < 1 \iff \frac{2}{u} + \frac{\log_2 u}{u} < 1 . 2 u \frac{2}{u} is a decreasing function for u > 0 u > 0 and it is a trivial calculus exercise to prove that log 2 u u \frac{\log_2 u}{u} is decreasing for u > e u > e . Thus overall the expression is decreasing and checking for u = 4.5 u = 4.5 (which corresponds to n = 9 n=9 ) we see that indeed 2 u + log 2 u u < 1 \frac{2}{u} + \frac{\log_2 u}{u} < 1 and as it is decreasing, it must hold for all u > 4.5 u > 4.5 too.

Sándor Daróczi
Jun 5, 2018

Note that n n can't be odd, otherwise at x = π x = \pi we would have sin n x + cos n x = 0 n + ( 1 ) n = 1 < 1 n \sin^n x + \cos^n x = 0^n + (-1)^n = -1 < \frac1n . Hence we might assume that n n is even.

Let f n ( x ) = sin n x + cos n x . f_n(x) = \sin^n x + \cos^n x. Our goal is to find the minimum of f n f_n . Computing the derivative yields f n ( x ) = n sin n 1 x cos x + n cos n 1 x ( sin x ) = n ( sin n 1 x cos x cos n 1 x sin x ) f_n(x)' = n\sin^{n-1} x \cos x + n\cos^{n-1} x (-\sin x) = n(\sin^{n-1} x \cos x - \cos^{n-1} x \sin x ) . Clearly the function can only have minimum value where its derivative equals zero, therefore we get the equation

n ( sin n 1 x cos x cos n 1 x sin x ) = 0 n(\sin^{n-1} x \cos x - \cos^{n-1} x \sin x) = 0

sin n 1 x cos x cos n 1 x sin x = 0 \sin^{n-1} x \cos x - \cos^{n-1} x \sin x = 0

sin x cos x ( sin n 2 x cos n 2 x ) = 0 \sin x \cos x (\sin^{n-2} x - \cos^{n-2} x) = 0

This can only be satisfied when either sin x = 0 \sin x = 0 or cos x = 0 \cos x = 0 , which implies x = k π 2 x = k\frac{\pi}{2} for k Z k \in \mathbb{Z} , or alternatively

sin n 2 x = cos n 2 x \sin^{n-2} x = \cos^{n-2} x

tan n 2 x = 1 , \tan^{n-2} x = 1,

where we assumed that cos x 0. \cos x \neq 0. This equation has solutions tan x = ± 1 \tan x = \pm 1 or x = π 4 + k π 2 x = \frac{\pi}{4} + k\frac{\pi}{2} , since n n is even.

Note that in the former case of x = k π 2 x = k\frac{\pi}{2} one of sin x \sin x and cos x \cos x is zero, and the other has absolute value of 1 1 . Therefore sin n x + cos n x = 0 n + ( ± 1 ) n = 1 1 n \sin^n x + \cos^n x = 0^n + (\pm 1)^n = 1 \geq \frac1n . However, in the latter case of x = π 4 + k π 2 x = \frac{\pi}{4} + k\frac{\pi}{2} the absolute value of both sin x \sin x and cos x \cos x equals to 1 2 \frac{1}{\sqrt{2}} , hence sin n x + cos n x = ( ± 1 2 ) n + ( ± 1 2 ) n = 2 2 n 2 = 2 1 n 2 . \sin^n x + \cos^n x = (\pm \frac{1}{\sqrt{2}})^n + (\pm \frac{1}{\sqrt{2}})^n = 2 \cdot 2^{-\frac{n}{2}} = 2^{1-\frac{n}{2}}. It follows that the minimum value of f n f_n is either 1 1 or 2 1 n 2 2^{1-\frac{n}{2}} .

In the first case the condition is clearly satisfied. However, in the second case sin n x + cos n x 1 n \sin^n x + \cos^n x \geq \frac1n only holds when 2 1 n 2 1 n 2^{1-\frac{n}{2}} \geq \frac1n or equivalently 2 n 2 n 2 . 2n \geq 2^{\frac{n}{2}}. Note that this is true whenever n 8 n \leq 8 . To show it doesn't hold for n > 8 n > 8 we employ induction. The base case n = 9 n =9 is clear. Assume that 2 n < 2 n 2 2n < 2^{\frac{n}{2}} for some n > 8 n > 8 . From the induction hyphothesis and the constraint n > 8 n > 8 we get

2 n + 1 2 = 2 2 n 2 > 2 2 n = 2 n + 2 ( 2 1 ) n > 2 n + 2 ( 2 1 ) 8 > 2 n + 2 = 2 ( n + 1 ) , 2^{\frac{n+1}{2}} = \sqrt{2} \cdot 2^{\frac{n}{2}} > \sqrt{2} \cdot 2n = 2n + 2(\sqrt{2}-1)n > 2n + 2(\sqrt{2}-1)8 > 2n+2 = 2(n+1),

since 128 > 81 8 2 > 9 2 1 > 1 8 16 ( 2 1 ) > 2. 128 > 81 \Rightarrow 8\sqrt{2} > 9 \Rightarrow \sqrt{2}-1 > \frac18 \Rightarrow 16(\sqrt{2}-1) > 2. The induction is therefore complete.

We have obtained that the condition of the problem only holds for even n 8 n \leq 8 . The greatest such n n is 8 8 , hence the solution.

A rigorous solution! Another approaching is using the Power Mean Inequality.Since n must be even,wlog,assume x [ 0 , π 2 ] x\in[0,\frac{\pi}{2}] .The case x = 0 , π 2 x=0,\frac{\pi}{2} doesn't matter. For x ( 0 , π 2 ) x\in (0,\frac{\pi}{2}) ,by Power Mean Inequality, ( s i n n x + c o s n x 2 ) 1 n ( s i n 2 x + c o s 2 x 2 ) 1 / 2 \displaystyle(\frac{sin^{n}x+cos^{n}x}{2})^{\frac{1}{n}}\ge (\frac{sin^{2}x+cos^{2}x}{2})^{1/2} (note that n 2 n\ge 2 ),or equivalently s i n n x + c o s n x ( 1 / 2 ) n 2 1 sin^{n}x+cos^{n}x\ge (1/2)^{\frac{n}{2}-1} .The equality is achieved when s i n x = c o s x = 2 / 2 sinx=cosx=\sqrt{2}/2 . The following step is exactly same...

Haosen Chen - 3 years ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...